Molecular remodeling of the renin-angiotensin system after kidney transplantation. (May 2017) - Antlanger, Marlies; Domenig, Oliver; Kovarik, Johannes J; Kaltenecker, Christopher C; Kopecky, Chantal; Poglitsch, Marko; Säemann, Marcus D
Objective: We aimed at assessing the molecular adaptation of the renin-angiotensin system (RAS) after successful kidney transplantation (KTX). Materials and methods: In this prospective, exploratory study we analyzed 12 hemodialysis (HD) patients, who received a KTX and had excellent graft function six to 12 months thereafter. The concentrations of plasma Angiotensin (Ang) peptides (Ang I, Ang II, Ang-(1–7), Ang-(1–5), Ang-(2–8), Ang-(3–8)) were simultaneously quantified with a novel mass spectrometry-based method. Further, renin and aldosterone concentrations were determined by standard immunoassays. Results: Ang values showed a strong inter-individual variability among HD patients. Yet, despite a continued broad dispersion of Ang values after KTX, a substantial improvement of the renin/Ang II correlation was observed in patients without RAS blockade or on angiotensin receptor blocker (HD: renin/Ang II R 2 = 0.660, KTX: renin/Ang II R 2 = 0.918). Ang-(1–7) representing the alternative RAS axis was only marginally detectable both on HD and after KTX. Conclusions: Following KTX, renin-dependent Ang II formation adapts in non-ACE inhibitor-treated patients. Thus, a largely normal RAS regulation is reconstituted after successful KTX. However, individual Ang concentration variations and a lack of potentially beneficial alternative peptides after KTX call for individualized treatment. The long-term post-transplant RAS regulation remains to be determined.